(untitled) (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2025)
The highlands of Abruzzo, including the Gran Sasso and Monti della Laga National Park and the Sirente-Velino Regional Park, are defined by towering peaks converging on vast plateaus. The geomorphological characteristics of these areas dictate specific forms of human interaction, such as pastoralism, agriculture, and forestry. The result is a landscape shaped by human practices and modes of occupation, centred on the communal use of resources and assets. This weave is evident not only in visible traces, such as those of ‘open fields’, but also in property and administrative traces, seemingly invisible yet strategically significant for accessing and exploiting the area’s resources. By analysing these locations in detail, we uncover a network of resources that, through the ‘design of the territory’, identifies the shared heritage of the mountain landscape. Can we think of the mountain as a single infrastructure? A weave constructed from countless relationships and contact zones where degrees of collaboration can be identified? This contribution seeks to explore a new way of reading and representing the mountain landscape. Through the observation and decoding of these traces, we can craft new spatial imaginaries and make hidden structures visible, expressing and reinterpreting the physical alphabet of anthropogeography. A single palimpsest, composed of deliberate layers, emerges, a weave that is drawn and thus designed.